Types and Contributing Factors of Social Conflicts in The Wanting Seed - Septiani, Amilia (Journal of Literature, Linguistics, & Cultural Studies, 2024)
Social conflict is a natural part of human existence, stemming from our inherent social nature and the inevitable clashes resulting from our interactions. Rooted in contradictions, differences, and competition of interests, social conflict permeates every layer of human society. It manifests among individuals, within groups, and across broader social environments. In literary works, authors often portray social conflicts, one of which is depicted in the novel The Wanting Seed by Anthony Burgess. This research aims to identify the types of social conflicts and the factors of social conflicts experienced by most of the characters or certain groups who have a central role in the novel The Wanting Seed by Anthony Burgess. The research adopts literary criticism and utilizes The Wanting Seed as the data source. The theoretical framework employed in this study is Lewis Coser's social conflict theory. The findings of this research are as follows: (1) three types of social conflicts are identified in The Wanting Seed novel, namely conflict involving social position, conflict of interest, and conflict of roles. (2) There are three factors causing social conflicts identified in The Wanting Seed novel: violence, relation, and condition. There is no social conflict in the novel The Wanting Seed which is caused by immolation.